Soil-applied selenite increases selenium and reduces cadmium in roots of Moringa oleifera - Zhiqiu Fu (Nature Portfolio, 2020)
Abstract Deficiency of selenium (Se) will lead to malnutrition and decreased immune function of the body. There is a common phenomenon of Se deficiency in foods. In this study, different concentrations of sodium selenite (Na2SeO3) were applied to Moringa oleifera grownin soil. The purpose was to explore the feasibility of Se biofortification of M. oleifera root. The effect of exogenous Se on the accumulation of Se and cadmium (Cd) in the roots of M. oleifera was studied by inductively coupled plasma mass spectrometry, and the mechanism of exogenous Se on the accumulation of Se and Cd in the roots was studied by Fourier transform infrared spectroscopy (FTIR) combined with principal component analysis and partial least squares regression analysis. The results showed that Na2SeO3 significantly affected the accumulation of Se and Cd in the roots (p < 0.05). The increase in Se was highest when Na2SeO3 was around 4.0 mg/kg, which increased by 315% compared with the control. The decrease in Cd was the lowest when Na2SeO3 was around 2.0 mg/kg, which decreased by 80% compared with the control. The results of FTIR analysis showed that Na2SeO3 treatment changed the carboxylate, phosphate radical, hemicellulose and protein in roots of M. oleifera, while the increase of Se was related to hemicellulose, protein, polysaccharide and lignin, and the decrease of Cd was related to hemicellulose and protein. The results showed that exogenous Se increased the accumulation of Se and inhibited the absorption of Cd. Therefore, the roots of M. oleifera can be used in Se biofortified products.